ANALISIS PEMASARAN BERAS ORGANIK BERSERTIFIKAT DAN NON ORGANIK DI DESA DLINGO KECAMATAN MOJOSONGO KABUPATEN BOYOLALI - suswadi; Kusriani Prasetyowati; Haryuni (JURNAL ILMIAH AGRINECA, 2021)
Marketing was an important thing in establishing the sustainability of the organic farming business because marketing was an economic activity that affects the high and low income of farmers. non-organic, the share of the price received by farmers in each rice marketing channel, and knowing the efficiency of rice marketing in Dlingo Village, Mojosongo District, Boyolali Regency. Taking as many as 30 respondents organic farmers and 30 non-organic farmers using the simple random sampling method (Simple Random Sampling Method). In addition to determining the respondents, traders used the method of scoping respondents (Tracing Sampling Method). Based on the results of the study are as follows: (1) The margins for each actor in the organic rice marketing channel are 38.74% farmer group level, 38.74% wholesaler level, and 22.52% modern market level. Meanwhile, the margins for each actor in the non-organic rice marketing channel are 72.86% for village collectors, 15.71% for wholesalers, 11.43% for retailers. (2) The benefits received by each actor in the organic rice marketing channel are: farmers enjoy 16% profit, farmer groups 39.4%, wholesalers 4.1%, and modern markets 40.2%. In the marketing channel of non-organic rice, farmers enjoy 7.4% profit, village collectors 70.4% and wholesalers 9.8%, retailers 12.4%. (3) The efficiency level in the organic rice marketing channel is 26.04% while the efficiency level in the non-organic rice marketing channel is 36.36%, meaning that both marketing channels are not efficient.